Learning English from Home during the Covid-19: Investigating Learners’ Experience for Online and Autonomous Learning - Tuti Hidayati; Faizatul Husna (Langkawi: Journal of The Association for Arabic and English, 2020)
Albeit the covid-19 pandemic impacts on education have been extensively discussed, little empirical evidence addresses students’ experience of autonomy. The present study investigates and obtains information about the experience that the students encountered during online English learning, their perception about it, and how their experience shapes their autonomous learning potentiality. The study was conducted in a quantitative approach adopting survey design and correlation procedure. Data was collected through an online form questionnaire. Data analysis was performed using both descriptive and inferential statistic to look for trends and correlation between the variables. The result of the study indicated that the students participating in the study seemed to have a quite good online English learning experience. They received various learning instructions and were engaged in different types of language learning activity. The majority of students perceived online English learning as fairly enjoyable, yet many of them displayed considerable potential to act as autonomous learners. Furthermore, the correlational analysis indicated a positive correlation (r=.312; sig=.008) demonstrating that students’ potentiality to learn autonomously to some extent, was influenced by their experience of online English learning. This study implies that both teachers and students gradually become more accustomed to online and autonomous learning.